Một số biện pháp bồi dưỡng học sinh giỏi môn Lịch sử trong dạy học các chủ đề Lịch sử thế giới (Lịch sử 10) - Nguyễn , Văn Ninh; Nguyễn , Thị Thu Phương (Tạp chí Giáo dục, 2023)
Improving education quality has always been the goal of the education sector in general and of high schools in particular. To improve education quality requires high schools to improve teaching quality as well as the effectiveness of fostering excellent students. Therefore, improving the quality of fostering excellent students in high schools is always considered a key task. On the basis of theoretical research, the article proposes a number of measures to foster effective history students in teaching 10th grade world history topics in high schools. This is a difficult and long-term task that requires a lot of effort and wisdom of the teacher, requiring each teacher to know how to find out, research, summarize experiences and measures to help students understand basic, focused and in-depth knowledge.